Perancangan Video Pembelajaran Matematika Keuangan Menggunakan Metode Multimedia Development Life Cycle (MDLC) - Tanjung, Rovidatul Hikmah; Damayanti, Fera (Algoritma: Jurnal Ilmu Komputer dan Informatika, 2025)
The advantages of learning videos are able to present independent learning with time flexibility and precisely leaving behind traditional teaching that relies on textbooks and lectures in the classroom. In addition, learning videos that are packaged with attractive visual elements such as the use of animation can increase students' motivation in learning. The purpose of this study was to design a financial mathematics learning video using the Multimedia Development Life Cycle (MDLC) method. This method consists of six stages, namely: concept, design, collection of materials, creation, testing, and distribution. Learning videos were tested using alpha testing and beta testing to assess the feasibility of the multimedia created. Alpha testing was carried out on two content experts with the results of the learning video feasibility of "Very High" so that it could be continued to the implementation stage. Beta testing was carried out by distributing questionnaires to an audience of 25 students and obtained a score above 85%, namely "Very Eligible" on all indicators. Overall, the test results showed that the financial mathematics learning video was considered feasible in terms of technical quality, visuals, content, support for independent learning, and increasing student learning motivation. Keywords: Learning Videos, Financial Mathematics, MDLC Method